A Multimodal Humidity Adaptive Optical Neuron Based on a MoWS2/VOx Heterojunction for Vision and Respiratory Functions - Syed, Abdul Momin (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.